OPTICAL AND MAGNETIC PROPERTIES OF TeO2⋅ZnO⋅Li2O GLASS SYSTEM CONTAINING NATURAL Fe3O4 PARTICLES - Widanarto, W; Sahar, M. R.; Shoshal, S. K.; Arifin, R.; Rohani, M. S. (BERKALA FISIKA, 2013)
Natural Fe3O4 particles obtained by extracting and manual pulverizing natural iron sand, are doped in the TeO⋅ZnO⋅Li2O glass system by melt quenching technique at 800 °C. X-ray diffraction spectra confirms the presence of iron sand particles with the 33-146 nm diameters and the glassy structure. Vibrating sample magnetometer reveals the pulverized sand exhibits paramagnetic behaviour with magnetic susceptibility of 2.76 × 10^-4 m^3 kg^-1. Incorporation of the particles in the glasses changes color, thermal stability and improve the glass formation ability through value of Tc-Tg. Ultraviolet–visible measurements show the optical energy band gap decreases by 1.58 eV. Meanwhile, the resonance amplitude of the electron spin resonance spectrum decreases due to the presence of Fe3O4 particles in reducing the unpaired electron spin. The synthesized glasses exhibit paramagneticbehavior.Keywords: Iron Sand, Ferrite oxide, Tellurite, Glass, Optical band gap, Magnetic property, ESR −Tcg